From emergency adaptation to institutional resilience: a policy and practice review of Somalia's health system, 1991–2026 - Nor Haji Osman; Hamdi Mohamud Osman; Abdifatah Nour Rage; Abdiweli Mohamed Abdi; Mohamed Ismail Iman; Aweys Ahmed Moallim; Abdirahman Mohamed Jimale; Mohamed Ahmed Ali; Ismail Dahir Ahmed; Abdikarim Abdi Adam; Abdirahman Ahmed Mohamud; Siham Mohamed Dhakane; et al. (Frontiers in Health Services, 2026)
Health-system resilience is a major policy concern in fragile and conflict-affected settings, where recurrent shocks intersect with chronic weaknesses in governance, financing, workforce, service delivery, information systems, and supply chains. This policy and practice review synthesizes 51 peer-reviewed and institutional sources published or issued between 1990 and 3 July 2026 to examine how Somalia's health system has responded to three decades of conflict, climatic emergencies, displacement, outbreaks, and humanitarian intervention. Sources were identified through targeted searches of PubMed/MEDLINE, Google Scholar, and authoritative institutional repositories and interpreted using the World Health Organization health-system building blocks and contemporary resilience concepts. The review distinguishes absorptive, adaptive, and transformative resilience from temporary emergency adaptation and donor-dependent response capacity using explicit decision rules concerning service continuity, duration, financing and ownership, integration into routine systems, and evidence of learning and accountability. Somalia has accumulated important resilience-enabling capacities, including community-based surveillance, outbreak-response learning, expansion of the District Health Information Software 2, national strategic planning, and the Community Health Strategy 2025–2029. However, chronic underfinancing, fragmented governance and service delivery, workforce shortages, weak supply chains, incomplete private-sector stewardship, inequitable access, and uneven primary health-care readiness continue to limit institutional resilience. The review proposes seven actionable priorities: a unified national resilience framework; predictable and aligned financing; primary health-care readiness and continuity planning; professionalized community health platforms; private-sector integration into regulation, referral, and reporting; climate-health, nutrition, and water, sanitation and hygiene preparedness; and an operational resilience dashboard linked to decision triggers and actor accountability. These priorities are policy inferences derived from Somalia-specific operational evidence, national strategies, and wider fragile-setting literature rather than causally proven interventions. Given binding fiscal and data constraints, implementation should be phased, costed, and begin with functions and indicators that can be sustained through existing routine systems. Somalia should therefore not yet be described as having a fully resilient health system. Durable resilience will depend on embedding recurrent emergency adaptations within financed, governed, measurable, equitable, and routinely functioning primary health-care and public-health institutions.